Eat, pray, love : one woman's search for everything - Gilbert, Elizabeth (Bloomsbury Publishing Plc, 2006)
t's 3 a.m. and Elizabeth Gilbert is sobbing on the bathroom floor. She's in her thirties, she has a husband, a house, they're trying for a baby - and she doesn't want any of it. A bitter divorce and a turbulent love affair later, she emerges battered and bewildered and realises it is time to pursue her own journey in search of three things she has been missing: pleasure, devotion and balance. So she travels to Rome, where she learns Italian from handsome, brown-eyed identical twins and gains twenty-five pounds, an ashram in India, where she finds that enlightenment entails getting up in the middle of the night to scrub the temple floor, and Bali where a toothless medicine man of indeterminate age offers her a new path to peace: simply sit still and smile. And slowly happiness begins to creep up on her.